Studying the influence of the scale factor on the parameters of mechoelectric transformations during elastic excitation of concrete; Russian Journal of Nondestructive Testing; Vol. 49, iss. 11 - Fursa T. V. Tatyana Viktorovna (2013, 2013)
Title screen